A multispecific monoclonal antibody G2 recognizes at least three completely different epitope sequences with high affinity. (4th September 2017) - Mahmud, Md. Nuruddin; Oda, Masayuki; Usui, Daiki; Inoshima, Yasuo; Ishiguro, Naotaka; Kamatari, Yuji O.
Abstract: A monoclonal antibody (mAb) G2 possesses an unusual characteristic of reacting with at least three proteins (ATP6V1C1, SEPT3, and C6H10orf76) other than its original antigen, chicken prion protein (ChPrP). The epitopes on ChPrP and ATP6V1C1 have been identified previously. In this study, we identified the epitope in the third protein, SEPT3. Interestingly, there was no amino acid sequence similarity among the epitopes on the three proteins. These epitopes had high binding affinities to G2 ( K D  = ∼10 −7 M for monovalent binding and K D  = ∼10 −9 M for divalent binding), as determined using a SPR biosensor. This is the first report on a three‐in‐one mAb recognizing completely different epitope sequences with high affinity. Additionally, competitive ELISA indicated that the binding sites on G2, specific for the three different epitopes, overlapped, suggesting that the antigen‐binding site may be flexible in the free form and capable of adapting to at least three different conformations to enable interactions with three different antigens.